2020
DOI: 10.3126/jnspoi.v4i2.34233
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of Adult Basic Life Support among Graduates in a Medical College of Kathmandu

Abstract: Introduction: Survival after sudden cardiac arrest depends upon early intervention, quality of cardiopulmonary resuscitation (CPR) and time of defibrillation. So, it is very important that at least the medical personnel know about Basic Life Support (BLS) as they are frequently facing the life threatening situations. Objective: To assess the level of awareness regarding adult basic life support among graduates in a medical college of Kathmandu. Methods: A descriptive cross-sectional study was condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…In our study, 51.6% of the participants received greater than 50% knowledge scores. This results in line with many studies in which medical students and interns showed adequate knowledge about BLS [14,17]. This result contradicts other research on medical students published in the literature, which revealed marginally lower knowledge levels of only 5% in Egypt, 17% in Pakistan, and 19% in the Netherlands, respectively [4,18,19].…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…In our study, 51.6% of the participants received greater than 50% knowledge scores. This results in line with many studies in which medical students and interns showed adequate knowledge about BLS [14,17]. This result contradicts other research on medical students published in the literature, which revealed marginally lower knowledge levels of only 5% in Egypt, 17% in Pakistan, and 19% in the Netherlands, respectively [4,18,19].…”
Section: Discussionsupporting
confidence: 75%
“…Health care professionals should possess sound knowledge and adequate skills to perform BLS [14]. This is because life-threatening emergencies can strike anytime, anywhere, and to anyone [15].…”
Section: Discussionmentioning
confidence: 99%
“…Many factors are cause of happening of these emergencies. These include a) the increase in age, b) Use of drug combinations, c) increase in number of dental procedures at the same time d) the increased quantities of drugs used in dentistry 9 .…”
Section: Discussionmentioning
confidence: 99%
“…Studies have revealed that most of medical and dental graduates felt the need of BLS training, very few have attended any skill workshop and were confident enough to execute the knowledge of BLS. [9][10] Therefore, dental students must have knowledge of basic life support maneuvers and skill to perform when needed. The fundamental principles of basic life support and a consideration of the management of common emergency medical conditions must be included of the dental education and training.…”
Section: Introductionmentioning
confidence: 99%